The gender wage gap among China's rural–urban migrants. Issue 1 (14th June 2020) - Wu, Yan; Pieters, Janneke; Heerink, Nico
Abstract: In this study, we present new empirical evidence on gender wage differences among rural–urban migrants in China. We use a data set that includes migrants residing in urban communities and those living at their workplaces—the latter were not included in the previous studies. We find that the gender wage gap among migrants is 16%–18% and does not differ between migrants living at workplaces and those living in urban communities. However, gender differences in industry sorting play a more important role for migrants living at their workplaces, whereas differences in education and experience are of importance for those living in urban communities. Overall, differences in the returns to characteristics are the main driver of the gender wage gap, especially for migrants living in urban communities.